Comparison of Forced Expiratory Volume in Six Seconds and FEV1/FEV6 ratio among Smokers and Non Smokers - Aneel Aslam; Abdul Waheed (Aziz Fatimah Medical and Dental College, 2021)
smokers and non -smokers Methodology: This cross sectional study of 200 subjects with age 18-25 years was carried out at Karachi based private medical college from August - October 2020. Prior the study ethical approval was taken. Male smokers and nonsmokers were included in the study. Male subjects with pulmonary diseases, cardiovascular diseases and any other skeletal deformities affecting respiration and females were excluded from the study. Height, weight and BMI were calculated. FEV6 was recorded by a calibrated digital spirometer following the protocol with three readings and highest reading was taken for analysis Results: This study was composed of 200 male participants. Of the total study population 83 (41%) were smokers and 117(59%) were non -smokers. Mean age of the study participants was 21.89 ± 4.8years Smokers have lower FEV6 and FEV1/FEV6 values as compared to non- smokers. Significant difference was observed in mean FEV6 of smokers and non-smokers (p- value =0.002). Mean FEV1/FEV6 was also significantly different among smokers and non- smokers (p- value = 0.000*) Conclusion: FEV6 and FEV1/FEV6 values were lower in smokers as compared to non -smokers reflecting decline in lung function.